2018
DOI: 10.1038/s41375-018-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel lncRNAs regulated by the TAL1 complex in T-cell acute lymphoblastic leukemia

Abstract: TAL1/SCL is one of the most prevalent oncogenes in T-cell acute lymphoblastic leukemia (T-ALL). TAL1 and its regulatory partners (GATA3, RUNX1, and MYB) positively regulate each other and coordinately regulate the expression of their downstream target genes in T-ALL cells. However, long non-coding RNAs (lncRNAs) regulated by these factors are largely unknown. Here we established a bioinformatics pipeline and analyzed RNA-seq datasets with deep coverage to identify lncRNAs regulated by TAL1 in T-ALL cells. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…TAL1 overexpression is thought to result in a sequestration of E-proteins into the TAL1-E-protein heterodimer and thus indirectly inhibit the transcription of genes regulated by E-protein-E-protein dimers [70]. In human and mouse T-ALL cells, the expression levels of RAG1, RAG2 and PTCRA are often repressed and can be upregulated after TAL1 knockdown [71][72][73]. Similarly, CD4, TCR-alpha and CD69 genes have been reported to be repressed by TAL1 [49,71,74].…”
Section: Inhibition Of E-protein Functions and Differentiation Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…TAL1 overexpression is thought to result in a sequestration of E-proteins into the TAL1-E-protein heterodimer and thus indirectly inhibit the transcription of genes regulated by E-protein-E-protein dimers [70]. In human and mouse T-ALL cells, the expression levels of RAG1, RAG2 and PTCRA are often repressed and can be upregulated after TAL1 knockdown [71][72][73]. Similarly, CD4, TCR-alpha and CD69 genes have been reported to be repressed by TAL1 [49,71,74].…”
Section: Inhibition Of E-protein Functions and Differentiation Blockmentioning
confidence: 99%
“…Our group has recently performed a comprehensive identification of lncRNAs expressed in TAL1-positive T-ALL cells by developing a bioinformatics pipeline and RNA-seq analysis with deep coverage [73]. We selected a list of putative lncRNAs that are directly activated by TAL1 and their regulatory complex partners.…”
Section: Lncrnas Regulated By Tal1 In T-allmentioning
confidence: 99%
“…Increasing evidence has suggested that lncRNAs are vital epigenetic regulators of mRNA expression and constitute an important fraction of the human transcriptome. Furthermore, there is a growing number of studies that have reported that lncRNAs play important roles in tumor genesis, progression, and metastasis, as well as many other cellular processes (13)(14)(15)(16). Aberrant expression of lncRNAs may contribute to glioma pathogenesis, including cellular proliferation, apoptosis, and metastasis (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…A major obstacle to understanding the mechanisms of T-ALL oncogenesis is the heterogeneous cellular and molecular nature of the disease, which is driven by a complex interplay of multiple oncogenic events. In this context, LncRNA signatures have been shown to define oncogenic subtypes [10] and several LncRNAs regulated by key T-ALL oncogenes have been identified [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%